Pengaruh Metode Quantum Teaching terhadap Pemahaman Materi Keberagaman di Kelas 4 SDN No 67/1 Sengkati Baru - Rahmawati, Rahmawati; Padlil, Padlil; Hidayati, Nur Afifah (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study aims to evaluate the impact of the Quantum Teaching method on the understanding of KEBERAGAMAN material in grade 4 at SDN No 67/1Sengkati Baru. Quantum Teaching is an instructional approach that focuses on actively engaging students through various learning styles, including visual, auditory, and kinesthetic. This research employs a quantitative experimental design to compare learning outcomes between students taught using the Quantum Teaching method and those taught using conventional methods. The sample consists of 25 students divided into two groups: one group using Quantum Teaching and the other using conventional methods. Data was collected through end-of-term tests to measure understanding of the material and analyzed using R Table validity test, ANOVA hypothesis testing, and frequency distribution of learning outcomes. The results indicate that all test items were valid, and there was a significant difference in learning outcomes between the two groups, with the Quantum Teaching group performing significantly better than the conventional method group. Additionally, the frequency distribution of learning outcomes shows that most students scored above average after implementing Quantum Teaching. The study also found that 80% of students preferred the Quantum Teaching method over the conventional method, indicating that this approach is more effective in enhancing student motivation and engagement in the learning process. These findings provide a strong basis for considering the implementation of Quantum Teaching as a superior alternative in primary school education.